"Let's Go to School and Marry Later": Tanzanian Girls' Schooling (1939–1976). Issue 1 (1st March 2023) - Wenzek, Florence
Abstract: In this article, I track the contribution of Tanganyikan girls to the big push for schooling that characterized the country, and the whole of Africa, from the 1940s to the late 1970s. So doing, I bring together two historiographies—works that document nationalist discourses that promoted this quick expansion of the schooling system and those that underline the agency of African girls in shaping their lives and education. Reading together girls' writings in the press, archival documentation, and interviews with adult women, I propose a nuanced analysis of girls' stances towards a public discourse that made their schooling a significant asset for nation-building.